Comparative study of the effect of hybrid nanoparticle on the thermal performance of cylindrical screen mesh heat pipe. (August 2016) - Ramachandran, R.; Ganesan, K.; Rajkumar, M.R.; Asirvatham, L.G.; Wongwises, S.
Abstract: The thermal performance of a cylindrical screen mesh heat pipe with hybrid nanofluid was experimentally investigated. The hybrid nanofluid was prepared by mixing Al2O3 and CuO nanoparticles with deionised water. The heat pipe was fabricated with straight copper tube of dimensions 300 mm length, 12.5 mm outer diameter and 1 mm thickness. The wick structure in the heat pipe was created by a three layer copper screen mesh of 100 mesh size. The heat input to the heat pipe was varied from 50 W to 250 W in five equal steps. The heat pipe was tested with three hybrid nanofluids made with combinations of Al2O3 and CuO nanoparticle in DI water (Al2O3 75%–CuO 25%, Al2O3 50%–CuO 50% and Al2O3 25%–CuO 75%). The tested hybrid nanofluids were made with 0.1% volume concentration of Al2O3 and CuO nanoparticle combination in deionised water. The results of the investigation showed that for the maximum heat load of 250 W considered in this work, the thermal resistance of the hybrid nanofluid with combination, Al2O3 25%–CuO 75%, showed 44.25% reduction compared to deionised water. The reduction in thermal resistance is due to the formation of porous coating on the wick surface which increases the wettability and surface roughness thereby creating more nucleation sites as seen in the SEM images. From the experimental investigation, it was observed that hybrid nanofluids are alternative to the conventional working fluids in heat pipes for electronic cooling applications.